2012
DOI: 10.1007/s10561-012-9296-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bioburden on human and animal tissues: Part 2—Results of testing of human tissue and qualification of a composite sample for routine bioburden determination

Abstract: A quantitative method was developed and validated to assess bioburden on tissue from human donors and to compare bioburden determination results to swab culture results from the same donor. An initial study with allograft tissue from 101 donors showed a wide range of bioburden levels; values from no colony-forming units (CFU) detected to >28,000 CFU were observed. Tissues from donors that had swab cultures negative for objectionable microorganisms generally had lower bioburden than tissues from donors where ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, bone swaps, biopsies, and rinsing the transplant only give a rough estimate of the actual bioburden. This might be a reason for the great variations of 0 to concentrations rarely as high as 3.9 × 10 4 cfu/g or cfu/mL, respectively, as reported by several working groups 62–64 . Therefore, the minimum concentration for the artificial contamination of bone blocks was 1 × 10 4 cfu/mL within this study.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…However, bone swaps, biopsies, and rinsing the transplant only give a rough estimate of the actual bioburden. This might be a reason for the great variations of 0 to concentrations rarely as high as 3.9 × 10 4 cfu/g or cfu/mL, respectively, as reported by several working groups 62–64 . Therefore, the minimum concentration for the artificial contamination of bone blocks was 1 × 10 4 cfu/mL within this study.…”
Section: Discussionsupporting
confidence: 49%
“…This might be a reason for the great variations of 0 to concentrations rarely as high as 3.9 Â 10 4 cfu/g or cfu/mL, respectively, as reported by several working groups. [62][63][64] Therefore, the minimum concentration for the artificial contamination of bone blocks was 1 Â 10 4 cfu/mL within this study. To efficiently determine the failure rate of high pressure decontamination, concentrations of up to 1 Â 10 8 cfu/mL were also tested.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, LEEI was shown to be an effective procedure for inactivation of viruses by Fertey et al 22 Kowalski et al observed a bioburden estimate of up to 2.8 × 10 4 CFU on human and animal tissue grafts. 49 The bioburden determined in this study exceeds this value by one log 10 level. This difference may originate from the high precautions taken during removal of tissue grafts compared with tissue removal for meat production.…”
Section: Discussionmentioning
confidence: 47%
“…[11] . Kowalski et al [12] carried out assessment of bioburden on tissue from 101 human donors and observed bioburden ranging up to > 28000 CFU. A number of studies have reported bacterial contamination of amniotic membrane [13,14] .…”
Section: Methods For Sterilization Of Tissue Allograftsmentioning
confidence: 99%